Green Marketing Attributes of Coffee Shops, Purchasing Interests, Lifestyles: What Really Affects Consumer Satisfaction? - Mazwan, M. Zul; Windiana, Livia; Mahdalena, Gigin; Widyastuti, Dyah Erni (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2023)
Green marketing strategies continue to grow as public awareness of environmental issues increases. Green marketing is applied to the marketing of environmentally friendly products including packaging and labeling with environmentally friendly standards. This study aims to learn the impact of green marketing strategies on purchasing interests and consumer satisfaction with coffee drinks in Malang, Indonesia. This study also explores the role of lifestyle in mediating the effect of green marketing on purchasing interest and consumer satisfaction. The sample is determined using the accidental sampling method with a sample size of 100 customers of Starbucks in Malang, Indonesia. The analytical method used is PLS (Partial Least Square). The findings show that green marketing strategies positively and significantly influence lifestyle, purchasing interest, and consumer satisfaction. The mediation variable (lifestyle) also positively and significantly influences purchasing interest and consumer satisfaction. Better green marketing strategy used will impact on how the community behaving in a healthy lifestyle, undoubtedly affecting the increase in buying interest and consumer satisfaction.